Inhibitory effect of indole analogs against Paenibacillus larvae, the causal agent of American foulbrood disease. Issue 5 (17th October 2017) - Alvarado, Israel; Margotta, Joseph W; Aoki, Mai M; Flores, Fernando; Agudelo, Fresia; Michel, Guillermo; Elekonich, Michelle M; Abel-Santos, Ernesto
Abstract: Paenibacillus larvae, a Gram-positive bacterium, causes American foulbrood (AFB) in honey bee larvae ( Apis mellifera Linnaeus [Hymenoptera: Apidae]). P. larvae spores exit dormancy in the gut of bee larvae, the germinated cells proliferate, and ultimately bacteremia kills the host. Hence, spore germination is a required step for establishing AFB disease. We previously found that P. larvae spores germinate in response to l -tyrosine plus uric acid in vitro. Additionally, we determined that indole and phenol blocked spore germination. In this work, we evaluated the antagonistic effect of 35 indole and phenol analogs and identified strong inhibitors of P. larvae spore germination in vitro. We further tested the most promising candidate, 5-chloroindole, and found that it significantly reduced bacterial proliferation. Finally, feeding artificial worker jelly containing anti-germination compounds to AFB-exposed larvae significantly decreased AFB infection in laboratory-reared honey bee larvae. Together, these results suggest that inhibitors of P. larvae spore germination could provide another method to control AFB.